1984
DOI: 10.1021/jm00376a009
|View full text |Cite
|
Sign up to set email alerts
|

Dichloro[1,2-bis(4-hydroxyphenyl)ethylenediamine]platinum(II) complexes: an approach to develop compounds with a specific effect on the hormone-dependent mammary carcinoma

Abstract: Stereoisomeric dichloro [1,2-bis(4-hydroxyphenyl)ethylenediamine]platinum(II) complexes (meso-3a, (+/-)-3b, (+)-3c, (-)-3d) and their N,N'-dibutyl derivatives (meso-4a, (+/-)-4b, (+)-4c, (-)-4d) were synthesized and tested on antitumor activity. The most active compound, 3d, shows a modest inhibition of the [3H]estradiol receptor interaction and causes a marked effect on the growth of the hormone-dependent human MCF 7 breast cancer cell line. It is also active on the hormone-independent human MDA-MB 231 breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…The first compounds of this sort to be prepared, a series of seteroisomers of dichloro[1,2-bis(4-hydroxyphenyl)ethylenediamine]platinum(II), competed with estrogen for interaction with the ER, but were toxic to ER+ and ER− cells alike. 127 Subsequent substitution at the 2 and 6 positions of the two phenyl rings with chlorine atoms, a substitution that had been shown to increase the affinity of the ligand for the ER, 128 produced a set of complexes that not only interacted with the ER but also selectively killed ER+ mammary carcinoma cells. 129 Variations on the substitutions of the nitrogen atoms and ring carbon atoms can influence estrogenicity and cytotoxicity, but often in a mutually exclusive manner.…”
Section: Platinum(ii) Compounds With a Mechanism Of Action Similarmentioning
confidence: 99%
“…The first compounds of this sort to be prepared, a series of seteroisomers of dichloro[1,2-bis(4-hydroxyphenyl)ethylenediamine]platinum(II), competed with estrogen for interaction with the ER, but were toxic to ER+ and ER− cells alike. 127 Subsequent substitution at the 2 and 6 positions of the two phenyl rings with chlorine atoms, a substitution that had been shown to increase the affinity of the ligand for the ER, 128 produced a set of complexes that not only interacted with the ER but also selectively killed ER+ mammary carcinoma cells. 129 Variations on the substitutions of the nitrogen atoms and ring carbon atoms can influence estrogenicity and cytotoxicity, but often in a mutually exclusive manner.…”
Section: Platinum(ii) Compounds With a Mechanism Of Action Similarmentioning
confidence: 99%
“…The stereoselectivity was similar to that observed with breast cancer cells: This study was a continuation of our attempts to optimize the antitumor activity of [S,S/R,R-1,2-diamino-1,2-bis(4-fluorophenyl)ethane]dichloroplatinum(II) ((R,R/S,S)-4F-Ph/4-Ph-PtCl 2 ). (R,R/S,S)-4F-Ph/4-Ph-PtCl 2 showed high activity in vitro and in vivo against a wide range of murine tumors, [7,8] and was more active than cisplatin and its R,S/S,R-configured diastereomeric congener. The attempt to optimize the antitumor activity of (R,R/S,S)-4F-Ph/4-Ph-PtCl 2 failed because of a separation of enantiomers.…”
Section: Structural Characterizationmentioning
confidence: 98%
“…[7,8] However, the attempt failed to increase the antiproliferative effects by separation into enantiomerically pure compounds. [9] In an earlier study, we demonstrated the increase of in vitro cytotoxicity by the exchange of one 4-fluorophenyl residue with a methyl (4F-Ph/Me-PtCl 2 ), ethyl (4F-Ph/Et-PtCl 2 ) or propyl group (4F-Ph/ Prop-PtCl 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Schonenberger and co-authors have reported upon the ability of ethylenediamine derivatives and their Pt(II) complexes to bind to estrogen receptors, being active against hormone-dependent mammary carcinoma resistant to cisplatin (25)(26)(27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%